DOP73 Efficacy and safety of escalation to tofacitinib 10 mg BID for patients with UC following loss of response on 5 mg BID maintenance therapy: Results from OCTAVE open-label, long-term extension study. (15th January 2020) - Sands, B E; Moss, A C; Armuzzi, A; Marshall, J K; Lindsay, J O; Sandborn, W J; Danese, S; Zeroncio, M; Modesto, I; Salese, L; Lawendy, N; Zhang, H; et al.
Abstract: Background: Tofacitinib is an oral, small-molecule JAK inhibitor for the treatment of ulcerative colitis (UC). The efficacy and safety of tofacitinib have been demonstrated in patients with moderate to severe UC in three Phase 3 studies (OCTAVE Induction 1 and 2 [NCT01465763; NCT01458951]; OCTAVE Sustain [NCT01458574]) [1]. Here, we present updated efficacy and safety data of tofacitinib dose escalation in patients with UC participating in an ongoing, open-label, long-term extension (OLE) study (OCTAVE Open, NCT01470612) [2]. Methods: We present updated data from the dose-escalation subpopulation of the OLE study (as of May 2019; database not locked) comprising patients who achieved clinical response (CR) following 8 weeks of tofacitinib 10 mg twice daily (BID) induction therapy, entered OCTAVE Sustain receiving tofacitinib 5 mg BID, experienced treatment failure between Week 8 and Week 52, and subsequently entered OCTAVE Open with escalation to tofacitinib 10 mg BID. Treatment failure was defined as an increase of ≥3 points from maintenance study baseline total Mayo score, plus an increase of ≥1 point in both rectal bleeding subscore and centrally read endoscopic subscore (ES), and an absolute ES of ≥2 after ≥8 weeks of maintenance therapy. CR, mucosal healing (MH) and remission (R) were evaluated at Months 2, 12, 24 and 36 of OCTAVE Open (non-responder imputation and last observation carried forward [NRI-LOCF] and observed data). Safety was evaluated throughout the study. Results: Of 944 patients enrolled in the OLE study, the dose escalation subpopulation comprised 59 patients. In these patients, CR, MH and R rates 36 months after dose escalation were, respectively, 40.7%, 39.0% and 30.5% for NRI-LOCF and 95.2%, 86.4% and 66.7% for observed data (Table). Of these 59 patients, 29 had prior tumour necrosis factor inhibitor (TNFi) failure; in these patients, CR, MH and R rates at Month 36 were, respectively, 51.7%, 51.7% and 41.4% for NRI-LOCF, and 100.0%, 92, 3% and 75.0% for observed data. Incidence rates for safety events and pt-years' exposure are reported in the table. Conclusion: For most patients who lost initial CR to tofacitinib 10 mg BID induction therapy while on tofacitinib 5 mg BID maintenance therapy, including those with prior TNFi failure, dose-escalation back to 10 mg BID recaptured CR by Month 2 and was generally maintained over 3 years. The safety profile with tofacitinib 10 mg BID in the dose-escalation subpopulation was generally consistent with that in the overall study population, although there was a numerically higher rate of herpes zoster. These analyses are limited by low pt numbers and the absence of a comparator arm. References: Sandborn WJ et al. N Engl J Med 2017;376:1723–36 Lichtenstein GR et al. United European Gastroenterol J 2019;7:Abstract OP213